Denitrification of Permeable Sand Sediment in a Headwater River Is Mainly Influenced by Water Chemistry, Rather Than Sediment Particle Size and Heterogeneity - Weibo Wang (MDPI AG, 2021)
Sediment particle size and heterogeneity play an important role in sediment denitrification through direct and indirect effects on, for example, the material exchange rate, environmental gradients, microbial biomass, and grazing pressure. However, these effects have mostly been observed in impermeable sediments. On the other hand, the material exchange of permeable sediments is dominated by advection instead of diffusion, with the exchange or transport rates exceeding those of diffusion by two orders of magnitude relative to impermeable sediments. The impact of permeable sediment particle size and heterogeneity on denitrification remains poorly understood, especially at the millimeter scale. Here, we conducted an in situ control experiment in which we sorted sand sediment into four homogeneous-particle-sizes treatments and four heterogeneous treatments. Each treatment was deployed, in replicate, within the riffle in three different river reaches with contrasting physicochemical characteristics. After incubating for three months, sediment denitrifier communities (nirS, nirK, nosZ), denitrification gene abundances (nirS, nirK, nosZ), and denitrification rates in all treatments were measured. We found that most of the denitrifying microbes in permeable sediments were unclassified denitrifying microbes, and particle size and heterogeneity were not significantly correlated with the functional gene abundances or denitrification rates. Water chemistry was the key controlling factor for the denitrification of permeable sediments. Water NO3−-N directly regulated the denitrification rate of permeable sediments, instead of indirectly regulating the denitrification rate of sediments by affecting the chemical characteristics of the sediments. Our study fills a knowledge gap of denitrification in permeable sediment in a headwater river and highlights that particle size and heterogeneity are less important for permeable sediment denitrification.